Population dynamics of cat shrimp (Mierspenaeopsis sculptilis) in the morning caught on the Samboja Kuala, Kutai Kartanegara Regency - Muhammad Hendrik Hendrawam; Abdunnur Abdunnur; Muhammad Syahrir Ramang (Jurnal Ilmu Perikanan Tropis Nusantara (Nusantara Tropical Fisheries Science Journal), 2024)
Samboja Kuala has a vast sea and abundant natural resources. East Kalimantan Province. The increase in capture fisheries certainly has a positive effect on fishermen, but it is necessary to know that an increase is always followed to carry out more intensive exploitation. Overfishing conditions allow for the catch of a number of stocks that exceed the amount needed in a waters. Various fishing gear used. The fishing gear used by fishermen to catch shrimp includes trawls. So far there are no specific catches that refer to the cat shrimp species (M. sculptilis) in Samboja Kuala waters, so studies or research are needed to provide information about the cat shrimp species population in these waters. The purpose of this study was to determine the estimated biomass and distribution of cat shrimp caught during the day in the Samboja Kuala sea and abundant natural resources, Kutai Kartanegara Regency. This research was carried out in November-December 2023, by conducting identification in the laboratory and taking samples of shrimp operating in Samboja Kuala Waters. The average stock density of cat shrimp (M. sculptilis) obtained during the day was 17.98 kg/km² and an estimated value of 442.28 kg with an area surveyed of 30.75 km². Based on research caught during the day cat shrimp were evenly distributed to all stations, the highest number of shrimp caught was obtained at station 5 and station 13.